2018
DOI: 10.1098/rsbl.2017.0743
|View full text |Cite
|
Sign up to set email alerts
|

Local extinction of the Asian tiger mosquito ( Aedes albopictus ) following rat eradication on Palmyra Atoll

Abstract: The Asian tiger mosquito, Aedes albopictus, appears to have been extirpated from Palmyra Atoll following rat eradication. Anecdotal biting reports, collection records, and regular captures in black-light traps showed the species was present before rat eradication. Since then, there have been no biting reports and no captures over 2 years of extensive trapping (black-light and scent traps). By contrast, the southern house mosquito, Culex quinquefasciatus, was abundant before and after rat eradication. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The atoll's 230 ha of land area consists of a ring of islets surrounding three central lagoons. Palmyra Atoll has a wet tropical climate (an average 4,488 mm annual rainfall; mean annual temperature 27°C) and approximately 90% of the atoll is forested, with canopies of five species which occur in monoculture to mixed‐stand gradients of Cocos nucifera (Arecaceae) (65% of total tree canopy area), Pisonia grandis (Nyctaginaceae) (12%), Scaevola taccada (Goodeniaceae) (12%), Heliotropium foertherianum (Boraginaceae) (12%), and Pandanus tectorius (Pandanaceae) (10%) (Lafferty et al., 2018; Young et al., 2010). Similar to many islands in the Pacific, it is believed that Cocos nucifera arrived from Asia with humans in the last 1,500 years (Gunn, Baudouin, & Olsen, 2011; Matisoo‐Smith & Robins, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The atoll's 230 ha of land area consists of a ring of islets surrounding three central lagoons. Palmyra Atoll has a wet tropical climate (an average 4,488 mm annual rainfall; mean annual temperature 27°C) and approximately 90% of the atoll is forested, with canopies of five species which occur in monoculture to mixed‐stand gradients of Cocos nucifera (Arecaceae) (65% of total tree canopy area), Pisonia grandis (Nyctaginaceae) (12%), Scaevola taccada (Goodeniaceae) (12%), Heliotropium foertherianum (Boraginaceae) (12%), and Pandanus tectorius (Pandanaceae) (10%) (Lafferty et al., 2018; Young et al., 2010). Similar to many islands in the Pacific, it is believed that Cocos nucifera arrived from Asia with humans in the last 1,500 years (Gunn, Baudouin, & Olsen, 2011; Matisoo‐Smith & Robins, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…For these models, we used the glmmTMB package (version 1.0.0) to accommodate the Tweedie distribution and compared marginal means with the emmeans package (version 1.4.5). To verify that changes in juvenile biomass were not due to environmental conditions in the years in which biomass could be assigned, we also ran a repeated measures ANOVA for juvenile tree numbers across all sampling years (2007–2010, 2014–2017) to verify that changes were consistent and compared annual precipitation (in cm) between pre‐ and post‐eradication years using a Mann–Whitney U test, (Lafferty et al., 2018, Appendix S4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, scientists have demonstrated that removing invasive rodents benefits native flora and fauna, particularly by increasing seabird fecundity [38,39]. Following rat eradication on Palmyra Atoll, the non-native Asian tiger mosquito (Aedes albopictus)-which was a known infectious disease vector-underwent a secondary local extirpation [40]. Additionally, recent scholarship suggests that coral reefs can benefit from the eradication of invasive rodents as seabirds enhance the productivity of coral reefs [37].…”
Section: Environmentmentioning
confidence: 99%
“…Records are sparser for invertebrate and plant losses on islands, but these are thought to be significant as well [19,20]. Indirect effects can also be important, as documented by high seabird densities increasing coral reef productivity on rat-free islands and rat removal also eliminating the disease vector mosquito Aedes albopictus [21,22]. Several features contribute to the vulnerability of island faunas to invasive mammalian predators [23].…”
Section: Introductionmentioning
confidence: 99%